John Rawls’ Justice as Fairness as a Common Good Principle: Critiques and Justification (London Journal of Research In Humanities and Social Sciences, 2025)
John Rawls concept of justice as fairness as a common good principle is founded on two arguments. The first argument concerns the critiques that were brought forth concerning Rawls conception of justice. They were done by philosophers who either supported or objected Rawls concept of justice as fairness, put differently, the critiques are either positive or negative. However, the bottom line is that they are both critical and constructive at the same time. Their critiques were basically directed to Rawls thought and position on Social Contract Theory, original position, the veil of ignorance, reflective equilibrium, priority of rights and liberties, two principles of justice, Rawls concepts on society, persons, social cooperation, social institutions and basic structure, primary goods just to mention a few. Some of the critiques were responded to by Rawls himself. The second argument concerns a justification as to why Rawls concept of justice as fairness is a common good principle. This is done firstly, by the author after considering the philosophers critiques and secondly through a philosophical analysis that encompasses constructive elements of Rawls conception of justice. The goal of this justification is to present Rawls sense of inclusivity, objectivity, commitment, mutual responsibility and cooperation as elements that are needed to foster and uphold the common good principle.
Keywords: educational inclusion; premature baby; child development; learning difficulty; justice.; Fairness; Common Good; Critiques; Justification